2019
DOI: 10.2169/internalmedicine.1332-18
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Biological Disease-modifying Antirheumatic Drug-free Condition of Adalimumab-treated Rheumatoid Arthritis Patients

Abstract: Objectives The present study was performed with the aim of analyzing the biological disease-modifying antirheumatic drug (bDMARD)-free (Bio-free) condition of adalimumab (ADA)-treated rheumatoid arthritis (RA) patients in a real-world setting. Methods ADA was used in the treatment of 130 (male, n=21; female, n=109 females) RA patients. Among them, 26 patients (20.0%) discontinued ADA due to a good response. We analyzed 20 patients who were followed up for more than 6 months after the discontinuation of ADA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Kurasawa et al reported the efficacy of adding another csDMARD to reduce the flare rate after the discontinuation of IFX ( 6 ). We also previously reported the importance of the additional administration of csDMARDs to obtain a good outcome after the discontinuation of adalimumab ( 13 ). In our study, four patients who experienced flare achieved remission again and maintained a Bio-free condition with the addition of csDMARDs.…”
Section: Discussionmentioning
confidence: 96%
“…Kurasawa et al reported the efficacy of adding another csDMARD to reduce the flare rate after the discontinuation of IFX ( 6 ). We also previously reported the importance of the additional administration of csDMARDs to obtain a good outcome after the discontinuation of adalimumab ( 13 ). In our study, four patients who experienced flare achieved remission again and maintained a Bio-free condition with the addition of csDMARDs.…”
Section: Discussionmentioning
confidence: 96%